Model Kolaborasi Guru PIAUD dan Guru PAI dalam Pengembangan Karakter Islami Pada Anak Usia Dini - Harefa, Zuraida; Ridha, Nikmatur (Prodi PIAUD STAI Sumatera Medan, 2025)
This study aims to describe the synergy between Early Childhood Islamic Education (PIAUD) teachers and Islamic Education (PAI) teachers in strengthening Islamic character education for early childhood learners at RA Muslimat Humene. This research is motivated by the importance of educator collaboration in building a strong foundation of moral values from an early age through integrated, continuous, and developmentally appropriate learning. The study employed a qualitative approach with a case study design conducted through in-depth interviews, participatory observation, and documentation analysis involving teachers, the school principal, and other educational stakeholders. The findings reveal that the synergy is reflected in three main aspects, namely collaborative planning of Islamic character-based learning, the implementation of structured habituation and moral role modeling, and the collaborative evaluation of children’s character development despite the absence of fully standardized indicators. Character-building strategies were implemented integratively through daily worship activities, moral habituation, religious educational games, and the strengthening of an Islamic learning environment. The impact of the synergy can be seen in the improved Islamic character behavior of children, such as speaking politely, sharing, praying, greeting, and obeying rules. However, challenges remain, including limited collaborative training, the absence of comprehensive character assessment tools, and the lack of formal documentation regarding collaboration. This study is expected to contribute to the development of a collaborative religious-based teaching model and to strengthen the system of Islamic character habituation in early childhood educational institutions.